Muslim Preacher’s persuasive strategy in da’wah communication to indigenous people (Orang Asli) in Selangor / Zulkefli Aini...[et.al] - Aini, Zulkefli; Don, Abd. Ghafar; Mokhtar, Ahmad Irdha; Ahmad Fauzi, Nur Uswah (Academy of Contemporary Islamic Studies, 2018)
The process of communication in delivering da’wah messages among the community of indigenous people (Orang Asli) demands da’wah efforts to guide positive changes towards the practice and appreciation of Islamic teachings. Therefore, this article is to identify muslim preacher’s persuasive strategy in da’wah communication to the community of indigenous people in Selangor. By using the theory developed by Achmad Mubarak who discussed persuasive communication from Islamic Da’wah perspective, the study is in fact a qualitative study with a case study design. Data collection was through semi-structured interviews. Some of seven research participants who were purposely selected comprising the Community Development Officers of Indigenous People or Penggerak Masyarakat Orang Asli (PMOA) and the Revert Preacher Panelist or Panel Dakwah Mualaf (PDM), two representatives from the Association of Welfare and Management Muslim Orang Asli Selangor or Persatuan Kebajikan dan Pengurusan Islam Orang Asli Selangor (PKPI) and al-Khalifah Foundation (Yayasan al-Khalifah) that has involved with preaching the indigenous people community. The data from interviews were analysed using thematic method which included the procedure of making transcription and reduction. The study found that the persuasive strategy of preachers in da’wah communications that took place involved the authority of preachers through the appointment and cooperation with Islamic institutions, the credibility of preachers namely knowledge, intentional preaching, spiritual practices and noble character and the application of indigenous people community changes that consisted of cognitive, behavioral and emotional aspects. Hence, the proponent approach as a strategy in da’wah communication of the indigenous people community can shape the thinking, appreciation and practice of the Islamic teachings willingly. The study, therefore may have implications for the government agencies such as the Department of Islamic Development Malaysia, State Islamic Religious Council and non-governmental organizations as an effort to enhance the effectiveness of da’wah movement among indigenous people community